2014
DOI: 10.1051/matecconf/20141501029
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Level of Awareness on Value Management Practice amongst Construction Developers

Abstract: Abstract. Construction Industry is one of the catalysts that enable such a nation economy to kept runs and grow from time to time. In this large and unique industry, the position of Architect, Engineer, Quantity Surveyor and Builders is the position that had been so familiar generally. Many of people do not aware with Value Management practice in Malaysia. Value Management may be described as a structured, analytical process for developing innovative holistic solutions to complex problems. The objective of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…VM can be applied to the construction sector as it helps to enhance the time, cost, and quality and increase the project's value for the client [19]. The survey conducted by Jaapar et al [20], Lop et al [21] found that 78 per cent of respondents are familiar with VM. However, after completing the training, just 16 per cent of respondents had a clear understanding of VM resulting in low implementation in Malaysia. Hence, the government approval of VM Circular 3/2009 by the Economic Planning Unit (EPU) in December 2009 has significantly impacted the procurement of government projects for projects more than RM50 million.…”
Section: Literature Review 21 Evolution Of Vmmentioning
confidence: 99%
“…VM can be applied to the construction sector as it helps to enhance the time, cost, and quality and increase the project's value for the client [19]. The survey conducted by Jaapar et al [20], Lop et al [21] found that 78 per cent of respondents are familiar with VM. However, after completing the training, just 16 per cent of respondents had a clear understanding of VM resulting in low implementation in Malaysia. Hence, the government approval of VM Circular 3/2009 by the Economic Planning Unit (EPU) in December 2009 has significantly impacted the procurement of government projects for projects more than RM50 million.…”
Section: Literature Review 21 Evolution Of Vmmentioning
confidence: 99%